Cytophotometric studies of cell populations - Bartels, P H; Olson, G B; Lockart, R; Wied, G L (Cell biophysics, 1980)
Technologic advances in the recording of digitized imagery have made the study of large cell populations by image analytical methods feasible. Computed image information provides quantitative, and novel, information that allows an exact measurement of minute changes in the chromatin distribution of cell nuclei, and the detection of subpopulations of cells or changes in the functional state of the cells. The sensitivity of the detection exceeds that of human observers; the specificity of the measured changes must be the subject of basic cell biologic research.